Bioactive and Biocompatible Macroporous Scaffolds with Tunable Performances Prepared Based on 3D Printing of the Pre‐Crosslinked Sodium Alginate/Hydroxyapatite Hydrogel Ink. Issue 4 (7th February 2019) - Liu, Shuifeng; Hu, Yang; Zhang, Jiancheng; Bao, Siqi; Xian, Lin; Dong, Xianming; Zheng, Wenxu; Li, Yiheng; Gao, Huichang; Zhou, Wuyi
Abstract: Bioactive and biocompatible porous scaffold materials with adjustable pore structures and drug delivery capability are one of the key elements in bone tissue engineering. In this work, bioactive and biocompatible sodium alginate (SA)/hydroxyapatite (HAP) macroporous scaffolds are facilely and effectively fabricated based on 3D printing of the pre‐crosslinked SA/HAP hydrogels followed by further crosslinking to improve the mechanical properties of scaffolds. The pore structures and porosity (>80%) of the porous scaffolds can be readily tailored by varying the formation conditions. Furthermore, the in vitro biomineralization tests show that the bioactivity of the porous scaffolds is effectively enhanced by the addition of HAP nanoparticles into the scaffold matrix. Furthermore, the anti‐inflammatory drug curcumin is loaded into the porous scaffolds and the in vitro release study shows the sustainable drug release function of the porous scaffolds. Moreover, mouse bone mesenchymal stem cells (mBMSCs) are cultured on the porous scaffolds, and the results of the in vitro biocompatibility experiment show that the mBMSCs can be adhered well on the porous scaffolds. All of the results suggest that the bioactive and biocompatible SA/HAP porous scaffolds have great application potential in bone tissue engineering. Abstract : Bioactive sodium alginate/hydroxyapatite porous gel scaffolds are facilely fabricated based on 3D extrusion printing of the pre‐crosslink hydrogel. This simple and effective method can be used to prepare a variety of functionalized porous materials, which are suitable for biomedical applications.